Assessment of hot flushes and vaginal dryness among obese women undergoing bariatric surgery. (2nd January 2016) - Goughnour, S. L.; Thurston, R. C.; Althouse, A. D.; Freese, K. E.; Edwards, R. P.; Hamad, G. G.; McCloskey, C.; Ramanathan, R.; Bovbjerg, D. H.; Linkov, F.
ABSTRACT: Objective Menopausal symptoms are associated with a negative impact on the quality of life, leading women to seek medical treatment. Obesity has been linked to higher levels of menopausal symptoms such as hot flushes. This assessment will explore whether the prevalence and bother of hot flushes and vaginal dryness change from pre- to post-bariatric surgery among obese midlife women. Methods This study is a longitudinal analysis of data from 69 women (ages 35–72 years) undergoing bariatric surgery with reported reproductive histories and menopausal symptoms at preoperative and 6-month postoperative visits. Prevalence of and degree of bother of hot flushes and vaginal dryness at pre- and post-surgery were compared using McNemar's test and Wilcoxon signed-rank test. Results The reported degree of bother of symptoms associated with hot flushes decreased from pre- to post-surgery ( p < 0.01). There was no significant change in the prevalence of hot flushes or vaginal dryness in the overall study sample. Conclusions The degree of bother of symptoms associated with hot flushes among midlife women may decrease after bariatric surgery. These results highlight important secondary gains, including less bothersome menopausal symptoms, for women who choose bariatric surgery for weight loss.